An ant mosaic revisited: dominant ant species disassemble arboreal ant communities but co-occur randomly - Majer, Jonathan; Sanders, N. J.; Crutsinger, G. M. (2007)
The spatial distributions of many tropical arboreal ant species are often arranged in a mosaic such that dominant species have mutually exclusive distributions among trees. These dominant species can also mediate the structure of the rest of the arboreal ant community. Little attention has been paid to how diet might shape the effects of dominant species on one another and the rest of the ant community. Here, we take advantage of new information on the diets of many tropical arboreal ant species to examine the intra- and inter-guild effects of dominant species on the spatial distribution of one another and the rest of the tropical arboreal ant community in a cocoa farm in Bahia, Brazil. Using null model analyses, we found that all ant species, regardless of dominance status or guild membership, co-occur much less than expected by chance.